Relation between broodstock number and spawning frequency and egg production of humpback grouper (Cromileptes altivelis) - M. Syaifudin; R.S. Aliah; . Muslim; K. Sumantadinata (Jurnal Akuakultur Indonesia)
This study was performed to determine spawning frequency, number of ovulated egg and spawning time of humpback grouper (Cromileptes altivelis) broodstock in hatchery.  Broodstock of 20-83 fish in weight of 1.5-2.0 kg were reared in circular concrete tank 225 m3.  The results showed that increasing in number of broodstock increases spawning frequency (R2= 0.694), and ovulated eggs number was also increased (R2= 0.828).  Spawning of humpback grouper can occur in the third to fourth week in every month.